SINTESIS DAN STRUKTUR KRISTAL KOMPLEKS TURUNAN TRIMETIL TIMAH KLORIDA SYNTHESIS AND CRYSTAL STRUCTURE OF COMPLEX COMPOUND OF TRIMETYLTIN CHLORIDE - ., Asrial (Jurnal Sainstek, 2007)
Trimetyltin-1,1,2,3,3- pentacyanopropenid compound is the stable organometall complex, which is macromolecules compound. This compound is synthesized from trimetyltinchlorid, (CH3)3SnCl, and silver pentacyanopropenid, AgC8N5, in water. This compound crystallized in orthorombic and in space group Pnnm. Crystal data show that: a = 7.794(1) , b = 10.821(1) , c = 11.462(1) pm; a = b = 90, g =103.84o; cell volume = 966.80 (16) 3. Compound structure arranged in two ion, namely [C3(CN)5]- anion and [(CH3)3]+ cation.